PENGGUNAAN WHATS APP BLAST UNTUK PENINGKATAN KEMAMPUAN BERBICARA MAHASISWA - Rudi Permadi (Program Studi Pendidikan Agama Islam, 2023)
Tasikmalaya Islamic Institute English students’ achievement stand in low category. Whats app blast play in improving students’ English achievement . The research was carried out to recognize the influence of whats app blast usage on the students’ English achievement. Experiment with one group pre test and post test factorial design is played as research methodology. Mulciple choice test ruled data collection. The number of sample is 60 students Islamic studies program IAI Tasikmalaya academic year 2022/2023. Random sampling works as technique of taking the sample. Data calculation and analysis concluded that Asymp. Sig. (2-tailed) =0.000 less than Asymp. Sig. (2-tailed) < 0.05 explaining that H0 is rejected. It means that there is a significant effect of whats’ app blast usage on the students’ English Achievement.